A four-year analysis of manuscripts submitted for publication in West African Journal of Medicine (June 2001 to May 2005) (2006)
There are various criteria that could be used to rate a tertiary institution. One of these is the productivity of the members of staff which is shown by the research conducted, publications submitted and manuscripts published in indexed journals. Manuscripts submitted and published in one of highly rated indexed journals in our locality were analysed with a view to identifying how the institutions add to knowledge by their contributions. Our findings show that the top-rated institutions in terms of manuscripts published in West Africa Journal of Medicine (WAJM) are University College Hospital (UCH), Ibadan, Univeristy of Ilorin Teaching Hospital (UITH), Obafemi Awolowo University Teaching Hospital (OAUTH), and Jos University Teaching Hospital (JUTH).